Majlis Syarahan Profesor by Dr. Hj. Mohd Sazili bin Shahibi: embracing digital culture in virtual university - Shahibi, Mohd Sazili (2023)
Full transcript of the Professorial Lecture by YBhg. Prof. Dr. Hj. Mohd Sazili bin Shahibi entitled “Embracing Digital Culture in Virtual University” held at Dewan Serbaguna Kolej Seroja, UiTM Shah Alam. Contains the emcee script, introduction of the speaker, and lecture content on digital culture and the virtual university.